Operating Leases as Second-tier Security Interests: A Continuing Case for Nemo Dat Under the Personal Property Securities Act 2009 (Cth) - Widdup, Linda (Butterworths, 2013)
Two-tiered security interests arise when a grantor grants a security interestin goods and then leases those goods to a third party which creates asecond security interest in the goods in favour of the grantor. If the grantorfails to perfect the second security interest and the lessee becomesinsolvent during the term of the lease, do both security interests vest in theinsolvent lessee by operation of s 267 of the PPSA? This article draws onCanadian case law to assist in the analysis of this issue under Australia’sPPSA and to illustrate a distinction between ‘in substance’ security interestsand deemed security interests in the form of operating leases. The articleargues the first-tier security interest does not vest in the insolvent lesseeeven though the second-tier security interest created by the operating leaseis unperfected on the relevant insolvency date. This conclusion is reachedby the application of the rules under the PPSA in conjunction with theprinciple of nemo dat quod non habet which, in this situation, is capable ofoperating concurrently with the PPSA to achieve a commercially acceptable result.